Correction of anemia in multiple myeloma patients by erythropoiesis-stimulating agents - N. A. Romanenko; N. A. Potikhonova; K. M. Abdulkadyrov (Онкогематология)
In this paper analysis of anemia correction efficacy in multiple myeloma patients was shown. Patients (n = 68) treated with epoetin alfa (recombinant erythropoietin (rEPO)) 150 IU/kg subcutaneously three times per week (no more 20 weeks) were included in the study group. Patients who did not receive erythropoiesis-stimulating therapy were included in the control group (n = 31). Patients in both groups received at least 3 courses of chemotherapy and continued to receive anticancer treatment during follow-up. Baseline hemoglobin level was 5.3 g/dl – 10.0 g/dl. The increase in hemoglobin level to normal range (≥ 12.0 g/dl) during ≤ 20 weeks was considered as positive therapy response. Positive response rate was higher in patients received epoetin alfa comparing with control group (64.7 % and 25.8 %, respectively; p < 0.05). Transfusion dependence persisted in 6 from 19 study patients who received RBC transfusions along with rEPO therapy (31.6 %), whereas in 5 from 9 control group patients (55.6 %). In epoetin alfa group significant increase in reticulocytes count at 2–3 weeks of therapywas revealed: from 27.3 × 109/l to 64.9 × 109/l (in patients with positive response) and from 13.3 × 109/l to 25.1 × 109/l (in patients without response). Changes in the reticulocytes count in the control group were not revealed. Thus in patients with positive response reticulocytes level significantly increased to 3 weeks of therapy compared with negative response patients (37.6 × 109/l versus 11.8 × 109/l, respectively; p < 0,05), it can be used as prognostic factors of rEPO response.